2013
DOI: 10.2147/dddt.s48500
|View full text |Cite
|
Sign up to set email alerts
|

Advances with microRNAs in Parkinson’s disease research

Abstract: Abstract:Parkinson's disease (PD) is the second-most common age-dependent neurodegenerative disorder and is caused by severe degeneration of dopaminergic neurons in the substantia nigra pars compacta. Unfortunately, current treatment only targets symptoms and involves dopamine replacement therapy, which does not counteract progressive degeneration. MicroRNAs (miRNAs) are a class of small RNA molecules implicated in post-transcriptional regulation of gene expression during development. Recent studies show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 105 publications
(126 reference statements)
0
15
0
Order By: Relevance
“…As an example, the list of miRNAs that target other PD-related genes such as LRKK2, Parkin and Pink becomes longer every year. Several reviews are available that illustrate the complex interplay of miRNAs in PD (Salta and De Strooper, 2012; Ma et al, 2013; Majidinia et al, 2016; Xie and Chen, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…As an example, the list of miRNAs that target other PD-related genes such as LRKK2, Parkin and Pink becomes longer every year. Several reviews are available that illustrate the complex interplay of miRNAs in PD (Salta and De Strooper, 2012; Ma et al, 2013; Majidinia et al, 2016; Xie and Chen, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Mutated leucine-rich repeat kinase2 (LRRK2) counteract let-7 miRNA due to which overexpressed E2F1 transcription factor leads to death of dopaminergic neuron. PD model of C. elegans also has low level of let-7 miRNA which was studied via microarray as well as qPCR techniques [17,36,37].…”
Section: Let-7 In Parkinson's Diseasementioning
confidence: 99%
“…Interestingly, the expression of SNCA mRNA is negatively regulated by at least two microRNAs, miR-7 and miR-153 (Doxakis, 2010;Junn et al, 2009) and DJ1 and Parkin expression has also been suggested to be connected to reduced miR-34b/c expression in late stage PD brain samples (Miñones-Moyano et al, 2011). While much more work is needed to elucidate which and how miRNAs are controlling PD-gene expression, the discovery that LRRK2 may more directly affect the expression and function of miRNAs themselves may suggest a more direct connection between PD and miRNA function (Ma et al, 2013;Mouradian, 2012).…”
Section: Misregulation Of Micrornasmentioning
confidence: 99%